The meaning of the term “timely” in the performance of management obligations concerning electronic money float funds - N. Farah; S. Widagdo; А. Sri Kusuma Dewi (Юридичний часопис Національної академії внутрішніх справ)
Digital transformation has brought significant changes to the financial industry, particularly in adopting electronic money systems in Indonesia, which have become a crucial payment instrument in the digital era. The purpose of this study was to analyse the vagueness of the term “timely” in Article 49, Paragraph (2), Letter c of Bank Indonesia Regulation No. 20/06/PBI/2018 “On Electronic Money”, which governs the obligations of electronic money issuers in managing float funds. By employing a normative legal research method, this study examined the grammatical and historical interpretation of the term “timely” to evaluate its impact on legal certainty. The interpretation method included an analysis of policy changes introduced into regulations by Bank Indonesia from the 2009 to 2018, highlighting the evolution of requirements and rules concerning the management of float funds. The findings indicated that the vagueness of the term “timely” has led to varying interpretations that affect electronic money issuers, users, and supervisory authorities, thereby creating legal uncertainty. These differing interpretations not only result in legal ambiguities but also can undermine user confidence in digital payment systems. Further analysis underscored the critical role of this term in ensuring the integrity and stability of the electronic money ecosystem. The lack of clarity regarding the timing of obligation performance highlights the necessity of establishing concrete time limits to minimise potential conflicts and uncertainties. This study recommended that regulators develop clearer guidelines for managing float funds in electronic money to enhance legal certainty and protect consumer interest. Establishing a concrete time standard for float fund management would support issuers in consistently performing their obligations and streamline the supervision process for regulatory authorities